Does Insurance Expansion Alter Health Inequality and Mobility? Evidence from the Mexican Seguro Popular - Joan Costa-i-Font; Frank Cowell; Belén Saénz de Miera Juárez (Center for Economic Studies and ifo Institute (CESifo), 2017)
The effect of insurance expansions on the distribution of health status is still a matter we know little about. This paper draws upon new measures of pure health inequality and mobility in health which accommodates categorical data to understand how an expansion of public insurance affects both inequality and mobility in health. These measures require a measure of health status that is either “upward-looking” or “downward looking”. We find that, the distribution of health worsens in Mexico between 2002 and 2009, although the change is only consistent for the upward looking definition of status. Together with the lack of mobility in health observed, we can thus conclude that Mexico is becoming more rigid over time insofar as the distribution of health status.
Keywords: I18; 330; self-reported health; health inequality; health mobility; health insurance; Mexico